Challenges to web-based learning in pharmacy education in Arabic language speaking countries - Alkoudmani, Ramez M.; Elkalmi, Ramadan Mohamed Mahmod (Wolters Kluwer - Medknow, 2015)
Web‑based learning and web 2.0 tools which include new online educational technologies (EdTech) and social media websites like Facebook ® are playing crucial roles nowadays in pharmacy and medical education among millennial learners. Podcasting, webinars, and online learning management systems like Moodle® and other web 2.0 tools have been used in pharmacy and medical education to interactively share knowledge with peers and students. Learners can use laptops, iPads, iPhones, or tablet devices with a stable and good Internet connection to enroll in many online courses. Implementation of novel online EdTech in pharmacy and medical curricula has been noticed in developed countries such as European countries, the US, Canada, and Australia. However, these trends are scarce in the majority of Arabic language speaking countries (ALSC), where traditional and didactic educational methods are still being used with some exceptions seen in Palestine, Kuwait, Jordan, Saudi Arabia, Egypt, UAE, and Qatar. Although these new trends are promising to push pharmacy and medical education forward, major barriers regarding adaptation of E‑learning and new online EdTech in Arab states have been reported such as higher connectivity costs, information communication technology (ICT) problems, language barriers, wars and political conflicts, poor education, financial problems, and lack of qualified ICT‑savvy educators. More research efforts are encouraged to study the effectiveness and proper use of web‑based learning and emerging online EdTech in pharmacy education not only in ALSC but also in developing and developed countries.